Goggatomy: A Method for Opening Small Cuticular Compartments in Arthropods for Physiological Experiments - Kay, Alan R.; Raccuglia, Davide; Scholte, Jon; Sivan-Loukianova, Elena; Barwacz, Christopher A.; Armstrong, Steven R.; Guymon, C. Allan; Nitabach, Michael N.; Eberl, Daniel F. (Frontiers in Physiology, 2016)
Most sense organs of arthropods are ensconced in small exoskeletal compartments that hinder direct access to plasma membranes. We have developed a method for exposing live sensory and supporting cells in such structures. The technique uses a viscous light cured resin to embed and support the structure, which is then sliced with a sharp blade. We term the procedure a ‘goggatomy’, from the Khoisan word for a bug, gogga. To demonstrate the utility of the method we show that it can be used to expose the auditory chordotonal organs in the second antennal segment and the olfactory receptor neurons in the third antennal segment of Drosophila melanogaster, preserving the transduction machinery. The procedure can also be used on other small arthropods, like mosquitoes and mites to expose a variety of cells.